Study on Effects of Reservoir Construction on Hydrological Regime of Downstream River Morphology Transition Area - CHEN Jian; CHEN Chen (Renmin Zhujiang)
Based on the construction of Capusilang hot spring reservoir and the characteristics ofmany water conservancy projects at thelower reach of hot spring reservoir and the transition frommountain river to plain river, this paper studies the influence of hot spring reservoirconstruction on the hydrological regime of the downstream river by combining one-dimensionalhydrodynamic calculation model with two-dimensional calculation hydrodynamic model. The resultsshow that the combination of the one-dimensional and two-dimensional hydrodynamic calculationmodel can objectively reflect the hydrodynamic changes in the transition area from the narrow anddeep mountain river channels at the upper reach to the broad, shallow and many-branch plain riverchannels at the lower reach, which is suitable for the study on the changes of hydrological regimein this area.Due to the storage and operation of the hot spring reservoir, in August of the floodseason,the flow of river channel at the lower reach of reservoir reduces significantly, with waterdepth, water width, and flow rate of river section decreasing obviously. In the main period ofagricultural irrigation(from March to June),the flow of river channel at the lower reach ofreservoir rises generally, with water depth, water width, and flow rate of river section increasingcorrespondingly. However, the construction of hot spring reservoir exerts little impact on thehydrological regime in the remaining months.